Xanthine Oxidase Inhibitors for Improving Renal Function in Chronic Kidney Disease Patients: An Updated Systematic Review and Meta-Analysis - Pisano, Anna; Cernaro, Valeria; Gembillo, Guido; D’Arrigo, Graziella; Buemi, Michele; Bolignano, Davide (International journal of molecular sciences, 2017)
Background: Accruing evidence suggests that Xanthine Oxidase inhibitors (XOis) may bring direct renal benefits, besides those related to their hypo-uricemic effect. We hence aimed at performing a systematic review of randomized controlled trials (RCTs) to verify if treatment with XOis may improve renal outcomes in individuals with chronic kidney disease (CKD). Methods: Ovid-MEDLINE, PubMed and CENTRAL databases were searched for RCTs comparing any XOi to standard therapy or placebo. The primary endpoint of interest was progression to End-Stage Kidney Disease (ESKD); secondary endpoints were changes in serum creatinine, glomerular filtration rate (eGFR), proteinuria and albuminuria. Results: XOis treatment significantly reduced the risk of ESKD compared to the control (3 studies, 204 pts; RR = 0.42; 95% CI, 0.22, 0.80) and also improved eGFR in data pooled from RCTs with long follow-up times (>3 mo.) (4 studies, 357 pts; mean difference (MD) 6.82 mL/min/1.73 m2; 95% CI, 3.50, 10.15) and high methodological quality (blind design) (3 studies, 400 pts; MD 2.61 mL/min/1.73 m2; 95% CI, 0.23, 4.99). Conversely, no definite effects were apparently noticed on serum creatinine, proteinuria and albuminuria. Conclusions: XOis may represent a promising tool for retarding disease progression in CKD patients. Future trials are awaited to confirm the generalizability of these findings to the whole CKD population.